2005
DOI: 10.1021/jp0463518
|View full text |Cite
|
Sign up to set email alerts
|

Rovibrational Energy Transfer in the 4νCHManifold of Acetylene Viewed by IR−UV Double Resonance Spectroscopy. 2. Perturbed States withJ= 17 and 18

Abstract: Collision-induced state-to-state molecular energy transfer between rovibrational states in the 12,700 cm(-1) 4nu(CH) manifold of the electronic ground state X of acetylene (C(2)H(2)) is monitored by time-resolved infrared-ultraviolet double resonance (IR-UV DR) spectroscopy. Rotational J-states associated with the (nu(1) + 3nu(3)) or (1 0 3 0 0)(0) vibrational combination level, initially prepared by an IR pulse, are probed at approximately 299, approximately 296, or approximately 323 nm with UV laser-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(151 citation statements)
references
References 140 publications
10
141
0
Order By: Relevance
“…19,20 The local perturbation at J = 12 revealed here agrees well with such statement. The perturbations starting at the J = 8 level can be more easily identified from Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…19,20 The local perturbation at J = 12 revealed here agrees well with such statement. The perturbations starting at the J = 8 level can be more easily identified from Fig.…”
Section: Resultssupporting
confidence: 89%
“…The well-known splits of the J = 17 and J = 18 levels were first reported by Smith and Winn, 7 and later attracted more studies. 8,9,11,12,15,20 In our spectrum recorded under very low sample pressures, the doublets are well resolved and the R(16) and R (17) Table I. Smith and Winn 7 have proposed candidates for the perturber as (2ν 1 + 3ν 2 + ν 1 5 ) or (3ν 2 + 2ν 3 + ν 1 5 ).…”
Section: Resultsmentioning
confidence: 65%
“…8,32 Key issues such as these will be addressed in subsequent papers. 33 In the meantime, the present "foundation studies at low J" (to which the subtitle of this paper alludes) have demonstrated the attention to detail that is essential in IR-UV DR experiments that seek unambiguous characterization of the rovibrational dynamics of a small but not-so-simple polyatomic molecule such as C 2 H 2 .…”
Section: Conclusion: Implications For Rovibrational Dynamicsmentioning
confidence: 88%
“…Figure 3 is representative of an extensive body of IR-UV DR kinetic results that can be satisfactorily simulated by a phenomenological master-equation model. 32,33 The majority of IR-UV DR measurements presented in this paper are performed with the UV PROBE tuned to the 299 nm Α -˜1 Subsequent papers in this series 33 will explore the apparent energy-transfer gateway at J ) 12. They will also seek explanations of the unusual CIQCB effects 8,32 that underlie most of our 4ν CH IR-UV DR experiments, present additional IR-UV DR results for rovibrational levels with J > 12, and formulate spectroscopic and kinetic models of observed results.…”
Section: The Central Issue: Apparently Anomalous Odd-∆j Retmentioning
confidence: 99%
See 1 more Smart Citation